Tech trends of the 4th industrial revolution - Pyo, Dong-Jin; Hwang, Jaejin; Yoon, Youngjin (Mercury Learning and Information, 2021)
The term "4th Industrial Revolution" has become commonplace, popping up in various media, but the public's understanding of the underlying technologies is often lagging the fast-pace of its related technological developments. This book is designed to bridge the gap which exists between the 4th industry-related technology boom and the general public's perception of it. The book introduces the content and applications of the related major technologies, such as the Internet of Things, blockchain, artificial intelligence, cloud computing, and big data - all considered essential for the development and operation of contemporary business models. It is written to minimize technical / engineering content in order to enhance the reader's ability to understand these topics.FEATURES:Introduces the content and applications of the related major technologies, such as the Internet of Things, blockchain, artificial intelligence, robotics, machine learning, cloud computing, big data, virtual reality, and moreProvides interesting descriptions and applications of technical topics to enhance understandingCovers topics and trends that must be considered in modern business models.